Merrifield resin-linked polyazole-based sorbent for heavy metal ions extraction from water - Zviagin, I.M.; Khimchenko, S.V.; Blank, T.A.; Shcherbakov, I.B.-Kh.; Bryleva, E.Yu.; Bunina, Z.Yu.; Sofronov, D.S.; Belikov, K.N.; Chebanov, V.A. (Functional Materials, 2018)
A new sorbent for heavy metal ions, that contains links with fragments of 1,2,3-triazole, 1,2,3- and 1,2,4-triazole, both triazoles and tetrazole was developed and appropriate procedures for the synthesis of these links were described. The obtained polymer is able to form stable complexes with the ions of heavy metals, such as Eu(III), Cd(II), Pb(II), Cu(II), Sr(II). The extraction rate dependence on the age of the sorbent, concentration of the cations, pH, and concentration of competing anions was studied.